MENINGKATKAN KETERAMPILAN GURU SEKOLAH DASAR DALAM MENETAPKAN KRITERIA KETUNTASAN MINIMAL MELALUI WORKSHOP DI SD - shobirin shobirin (Jurnal Tunas Pendidikan, 2021)
This study aims to describe the process of determining minimum completeness criteria through workshops, as well as to improve teachers' skills in determining minimum completeness criteria through workshops at SD Negeri 73 / II Simpang Sungai Mancur. In addition, this study also aims to describe the teacher's response to the activities undertaken. This research is classified as a supervisory action research involving 8 teachers. The research was conducted in two cycles and each cycle consisted of 4 stages, namely: planning, implementing, observing and reflecting. The determined performance indicators are: if at least 85% of the teachers are classified as very good and good in the aspect of determining the minimum completeness criteria, then it can be said that the action implemented is successful. Aspects that are measured in assessing the success of the action are the readiness of the teacher to attend the workshop and the results of the workshop. From the analysis, it was found that there was an increase in the readiness and performance of teachers in determining the minimum completeness criteria from cycle I to cycle II. Achievement of performance indicators is found in action II. Therefore it can be concluded that through workshops can improve teacher skills in determining minimum completeness criteria at SD Negeri 73 / II Simpang Sungai Mancur. Thus, it can be suggested to supervisors or other researchers that workshop activities can be used as an alternative in improving teacher skills in determining minimum completeness criteria.